2019
DOI: 10.1109/access.2019.2937571
|View full text |Cite
|
Sign up to set email alerts
|

Knock Detection Based on Recursive Variational Mode Decomposition and Multilevel Semi-Supervised Local Fisher Discriminant Analysis

Abstract: Knock is an abnormal combustion phenomenon in gasoline engines. Strong knocks will reduce the efficiency and durability of engine, while with slight knocks engines can run on a high-efficiency state. It is necessary to detect knock and control the state of knock in order to improve the thermal efficiency of engine. This paper proposes a novel approach for detecting engine knocks in various intensities based on vibration signal of engine block using variational mode decomposition (VMD) and semi-supervised local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The results indicated that the knock detection accuracy was 97%. AAn approach for detecting engine knocks inof various intensities based on the vibration signal of an engine block using VMD and semi-supervisedsemisupervised local fisherFisher discriminant analysis was proposed in [3], and the classification rate forof strong knocks was over 95%. As mentioned above, there is much room for improvement in the denoising performance and accuracy.…”
Section: Completed Files By Springer Nature Author Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that the knock detection accuracy was 97%. AAn approach for detecting engine knocks inof various intensities based on the vibration signal of an engine block using VMD and semi-supervisedsemisupervised local fisherFisher discriminant analysis was proposed in [3], and the classification rate forof strong knocks was over 95%. As mentioned above, there is much room for improvement in the denoising performance and accuracy.…”
Section: Completed Files By Springer Nature Author Servicesmentioning
confidence: 99%
“…In recent years, VMD has been introduced for noise analyses of rotating machines and as [8,28,35]. Although signals are separated into a series of IMFs, IMFs depend on the values of the balancing parameter and the number of modes that are adjustable, and the results may be inaccurate when they are not set in place [3]. Therefore, an optimization method utilizing GA is proposed in this work to solve the problem of parameter optimization.…”
Section: Signal Denoisingmentioning
confidence: 99%
“…where TP i represents the number of true positive instances, FP i represents the number of false positive instances, FN i represents the number of false negative instances and i = 1, 2, 3, 4 represents the four faults in table 1. As shown in (22), the F-measure index contains information about the precision rate and recall rate, whose value ranges from 0 (worst) to 1 (best) [51].…”
Section: Fault Isolation Capabilitymentioning
confidence: 99%
“…However, we consider the SAE-based CS method a sparse representation method to obtain a compressed matrix and perform further FDI work. Compared with the traditional DR method, PCA [16][17][18], linear discriminant analysis [19], and Fisher discriminant analysis [20][21][22] etc, this method does not require prior knowledge to obtain features and is easily operated.…”
Section: Introductionmentioning
confidence: 99%